VERNACULARIZATION IN MALAYSIAN TAFSIR: A STUDY OF TAFSIR NUR AL-IHSAN BY MUHAMMAD SA'ID AL-KEDAHI - Nuryatul Choiroh, Wahyuni (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
This article discusses vernacularization in Malay-Language Tafsir by examining Tafsir Nur al-Ihsan by Syaikh Muhammad Sa'id al-Qadhi al-Kedahi as an analytical study. This oldest tafsir was written in 1344H/1926M during the reign of the 21st Sultan of Kedah by a Qadhi in Kedah Malaysia, as well as the first Malaysian mufassir who interpreted the Qur'an in Javanese with Arabic alphabet letters. This research focuses on three main problems: how vernacularization is applied in the book of Tafsir Nur al-Ihsan in the linguistic, writing, and interpretation aspects. Through the theory of vernacularization, this research explains the implementation of vernacularization related to the phenomenon and the facts of the text that developed in the book of Tafsir Nur al-Ihsan. By using a qualitative approach through the literature study method, the results of this study show that; First, vernacularization in the linguistic aspect through the use of local languages commonly used by the local community in the use of the word